The nexus between research, policy and implementation - Zengele, Thulani (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper argues the perception that the distribution of rewards and incentives for researchers is not synchronous within academic wide values. Researchers are of the opinion that their work is not appropriately recognized by policy makers and is used as an alternative source of information. Consequently, this perception by researchers may tend to create animosity by researchers towards policy makers as dissertations, theses and published research articles accumulate dust in university and community library shelves. The evidence –based approach in policymaking and decision-making is adopted in this paper. The purpose of this research paper is to identify the significance and ways in which those who receive research funding could find ways of ploughing back into the communities they serve by working in collaboration with the policy formulators and the department of education in the articulation and implementation of policy initiatives. This is a conceptual article where research articles were used to formulate the argument presented in this article. My informed opinion is that when government education agencies do not heed the warnings of researchers, they not only fail to plan, but they end up planning to fail. This is because of the existing universal gap between research, policy formulation and implementation. For the nexus to exist indeed there must be meaningful and effective implementation of policies.